An Exploratory Study on the Influence of Salary Expectations on Graduate Employment - Naidoo, Kamara (The IIE, 2017)
For the past 14 years South Africa has been experiencing an unemployment rate above 20%. The purpose of the study was to investigate the influence of salary expectations on graduate unemployment - a factor that contributes to South Africa’s overall unemployment rate. A qualitative approach was adopted for this study, interviews were used to explore the trends in relation to graduates’ salary expectations and its influence on their employability, the influence of employers’ expectations and the role it plays in motivating employers to employ graduates was also investigated. The study also considered the influence of gender, race and attitudes. The researcher used the interviews to analyse the respondents’ response by analysing body language, tone and verbal reaction to questions asked. The results of the study concluded that the graduates have a naïve perception of the business environment and that they should remain open minded to opportunities presented by employers who are looking for enthusiastic, suitable qualified, entrants for their organisation.
Keywords: Unemployment; Salary scales; Graduate expectations